Horticulture based plasticulture-cum-covered cultivation for livelihood security - Singh, Awani Kumar; Sabir, Naved; Noopur, Kohima (Indian Horticulture, 2019)
The plasticulture-cum-protected cultivation is emerging as the most promising field, particularly in terms of higher productivity, quality, increased income, entrepreneurship etc. But the progress of area coverage under protected technologies is highly satisfying. Other major reasons for higher adoption include promotion of hi-tech horticulture by public financial institutions. Although, despite indubitable potential of protected cultivation, its spread has not been linked concomitantly with dissemination of technology, quality inputs, post-harvest management and processing units besides overall market linkages. Net result is that despite the technology performing exceedingly well by up-to-date farmers, majority of them keep facing challenges to cope up with the demands of hi-end horticulture.